2003
DOI: 10.1002/bem.10113
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a 50 Hz sinusoidal magnetic field on cell adhesion molecule expression in two human osteosarcoma cell lines (MG‐63 and Saos‐2)

Abstract: The possibility that a sinusoidal 50 Hz magnetic field with a magnetic flux density of 0.5 mT can induce variations in the expression of cell adhesion molecules (CAMs) in two human osteosarcoma cell lines (MG-63 and Saos-2) was investigated. In particular, the expression of two important integrins, VLA-2, the receptor for collagen, and VLA-5, the receptor for fibronectin, as well as CD44, were examined in both cell lines after these had been exposed for 7 and 14 days to a 50 Hz, 0.5 mT field. Cell surface morp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 45 publications
1
18
0
Order By: Relevance
“…D), which indicates that the exterior magnetic field improved the cell proliferation on both the MHA and HA scaffolds, consistent with previous research. 2,33,34 The most significant cell proliferation was found on the MHA scaffold with the exterior magnetic fields, suggesting a likely synergistic effect between the MHA and the exterior magnetic fields. A similar trend is observed for the MC3T3-E1 cells in Figure 7.…”
Section: Fda/pi Staining Assaymentioning
confidence: 94%
See 2 more Smart Citations
“…D), which indicates that the exterior magnetic field improved the cell proliferation on both the MHA and HA scaffolds, consistent with previous research. 2,33,34 The most significant cell proliferation was found on the MHA scaffold with the exterior magnetic fields, suggesting a likely synergistic effect between the MHA and the exterior magnetic fields. A similar trend is observed for the MC3T3-E1 cells in Figure 7.…”
Section: Fda/pi Staining Assaymentioning
confidence: 94%
“…The specimen was immersed into 100 mL of fluid and shaken ceaselessly at 37°C. A 2 mL aliquot of leaching solution was taken away at each time point (2,4,8, and 12 hours, and 1, 2, 3, and 5 days), while the same volume of fresh medium was simultaneously added back into the solution. The samples were further diluted eightfold for atomic absorption spectroscopy analysis to evaluate the iron content and calculate the masses of released magnetite.…”
Section: Stability Of Mha Scaffolds Under Biological Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the levels of expressed CD44 influence cell-cell interactions, cell adhesion and migration. According to Rudzki and Jothy (Rudzki & Jothy, 1997) and proposed mechanism of action by Santini, it is indicated that MF influence these molecules' expression, responsible for the transmission of vital signals, in the growth and metastasis of cancer (Santini et al, 2003).…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…The CAMs principally involved in these processes are those directed against important components of the extracellular matrix such as fibronectin, collagen, laminin, hyaluronan, heparan sulfate and elastin. Although a limited number of studies examining the effects of magnetic fields on cell adhesion are available, important insights into this issue have been previously provided (5).…”
Section: Introductionmentioning
confidence: 99%